1988
DOI: 10.1021/ja00218a041
|View full text |Cite
|
Sign up to set email alerts
|

Diels-Alder reaction of dienes having stereogenic allylic substituents: control of diastereoface selectivity by the dienophile

Abstract: with peptide carbonyls and the remaining ligands to cations and Supplementary Material Available: Anisotropic thermal pacocrystallized water molecules. rameters for non-hydrogen atoms, atomic coordinates of hydrogen atoms, bond lengths, and bond angles (5 pages); observed and Acknowledgment. This research was supported in part by NIH calculated structure factors (12 pages). Ordering information Grant GM30902.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…Evidence presented for this sequence of events centred on observations of a gradual improvement in p-diastereofacial selectivity with progressively larger silyl ether derivatives of chiral dienols. 8 Perhaps the most convincing support for the IMDA route in Scheme 1 is the exclusive formation of cis-fused lactone acids from pre-formed half ester derivatives of substituted maleic anhydrides. 10-14 Thus, White and Sheldon 10, 11 reported that heating a 50 : 50 mixture of citraconate half esters 9 and 10 in xylene at reflux produces a single crystalline product 11 in low yield along with a substantial quantity of polymer † Electronic supplementary information (ESI) available: synthetic procedures, characterisation details, selected time lapse 1 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence presented for this sequence of events centred on observations of a gradual improvement in p-diastereofacial selectivity with progressively larger silyl ether derivatives of chiral dienols. 8 Perhaps the most convincing support for the IMDA route in Scheme 1 is the exclusive formation of cis-fused lactone acids from pre-formed half ester derivatives of substituted maleic anhydrides. 10-14 Thus, White and Sheldon 10, 11 reported that heating a 50 : 50 mixture of citraconate half esters 9 and 10 in xylene at reflux produces a single crystalline product 11 in low yield along with a substantial quantity of polymer † Electronic supplementary information (ESI) available: synthetic procedures, characterisation details, selected time lapse 1 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…), as expected for maleimide dienophiles. 21 Access to these functionalized dienes traditionally requires differentiation of bifunctional starting materials using lengthy protecting group manipulation sequences. Alternatively, this dehydrogenation manifold provides direct access to 1,3-diene intermediates from mono-functional terminal olefins, the majority of which are generated in one step from commercial starting materials.…”
mentioning
confidence: 99%
“…The dienophile reacts at the more accessible π‐face of the diene; in the absence of overriding electronic effects, this will be on the side of the diene in which the smaller substituent resides. This model, which also explains the outcomes of inter molecular Diels–Alder reactions of acyclic chiral dienols and derivatives,29b, c is being further explored and tested.…”
Section: Closing Remarksmentioning
confidence: 99%